The Relationship between Corporate Governance and Firm Value of Listed Companies on The Stock Exchange of Thailand in SET100 Index - Sabsombat, Nuthawut; Sangthong, Kongpop; Yasaboo, Natnaree; Laddee, Nutthapol; Chukaew, Nisanon; Pongsri, Siwakorn (WMS Journal of Management, 2020)
The purpose of this research is to study the relationship between Corporate Governance (CG) and firm value measured by accounting approach and marketing approach of listed companies on the stock exchange of Thailand in SET100. Data are collected from listed companies on the stock exchange of Thailand in SET100 from 2017 to 2018. There are 200 firm-years in this study. Multiple regression analysis is used to examine the relationship between CG and firm value. The result shows that the proportion of director ownership has a positive relationship with firm value, which is measured by both accounting-based and marketing-based measurement. This is because directors who are simultaneously shareholders, determine more efficiently the company’s strategies, directors, and goals. Furthermore, the size of the board and the number of board director meetings have a negative relationship with the firm value measured by both accounting and marketing aspects. If companies have inordinate board members or excessive numbers of board meetings, they will have a negative impact on the director’s decision and lead to lower in firm value. The duality of the chairperson and the executive position is negatively related to firm value in which measured by marketing base. In other words, separation of board chairman and CEO can increase in firm value because there is decentralization that has a quasi-independent government. This research illustrates that CG is essential for building shareholders and investors’ confidence because implementing CG will provide a firm with efficient and transparent systems, and that can add to firm value and encourage the company’s sustainable growth.